East–West gradient in the incidence of inflammatory bowel disease in Europe: the ECCO-EpiCom inception cohort. Issue 4 (20th April 2013) - Burisch, J; Pedersen, N; Čuković-Čavka, S; Brinar, M; Kaimakliotis, I; Duricova, D; Shonová, O; Vind, I; Avnstrøm, S; Thorsgaard, N; Andersen, V; Krabbe, S; et al.
Abstract : Objective: The incidence of inflammatory bowel disease (IBD) is increasing in Eastern Europe. The reasons for these changes remain unknown. The aim of this study was to investigate whether an East–West gradient in the incidence of IBD in Europe exists. Design: A prospective, uniformly diagnosed, population based inception cohort of IBD patients in 31 centres from 14 Western and eight Eastern European countries covering a total background population of approximately 10.1 million people was created. One-third of the centres had previous experience with inception cohorts. Patients were entered into a low cost, web based epidemiological database, making participation possible regardless of socioeconomic status and prior experience. Results: 1515 patients aged 15 years or older were included, of whom 535 (35%) were diagnosed with Crohn's disease (CD), 813 (54%) with ulcerative colitis (UC) and 167 (11%) with IBD unclassified (IBDU). The overall incidence rate ratios in all Western European centres were 1.9 (95% CI 1.5 to 2.4) for CD and 2.1 (95% CI 1.8 to 2.6) for UC compared with Eastern European centres. The median crude annual incidence rates per 100 000 in 2010 for CD were 6.5 (range 0–10.7) in Western European centres and 3.1 (range 0.4–11.5) in Eastern European centres, for UC 10.8 (range 2.9–31.5) and 4.1 (range 2.4–10.3), respectively, and for IBDU 1.9 (range 0–39.4) and 0 (range 0–1.2), respectively. In Western Europe, 92% of CD, 78% of UC and 74% of IBDU patients had a colonoscopy performed as the diagnostic procedure compared with 90%, 100% and 96%, respectively, in Eastern Europe. 8% of CD and 1% of UC patients in both regions underwent surgery within the first 3 months of the onset of disease. 7% of CD patients and 3% of UC patients from Western Europe received biological treatment as rescue therapy. Of all European CD patients, 20% received only 5-aminosalicylates as induction therapy. Conclusions: An East–West gradient in IBD incidence exists in Europe. Among this inception cohort—including indolent and aggressive cases—international guidelines for diagnosis and initial treatment are not being followed uniformly by physicians.